Effectiveness of the Wasaka-Based Scientific Learning Design in Strengthening Students’ Performance Character in Physics Education - Abdul Salam; Agus Setiawan; Aminuddin Prahatama Putra; Yadi Ruyadi (Universitas Islam Negeri Antasari Banjarmasin, South Kalimantan, Indonesia, 2026)
This study examines the effectiveness of a physics learning design that integrates a scientific approach with Wasaka local wisdom to strengthen students’ performance character. The Wasaka (Waja Sampai Kaputing) philosophy emphasizes perseverance, diligence, and commitment in accomplishing academic tasks. A descriptive–quantitative method was applied to 30 physics education students. Hard work and perseverance were assessed using observation rubrics, while learning outcomes were measured through essay tests. Results revealed a significant improvement in performance character, with hard-work scores increasing from 1.49 to 4.86 and perseverance from 1.42 to 4.86, yielding an average gain of 0.96 (high). Learning outcomes also improved moderately (N-Gain = 0.43–0.55). The findings confirm that the Wasaka-based scientific design effectively enhances students’ work character through reflective and inquiry-oriented learning. These results imply that integrating local wisdom within scientific pedagogy provides a meaningful pathway for developing scientific and character-based competence in higher education.